Dynamic model of optimized supply for organizational units of armed forces (at decentralized procurement) - Sysoiev, Volodymyr V. (Economics and Business Review, 2013)
Efficient activity of organizational units in armed forces is impossible without comprehensive and continuous logistics. The key role in the arrangement of logistics is played by supply processes: ordering, purchase, delivery, and storage of material and technical resources (goods). The Complexity and multiplicity of implementing the logistics process assume the use of economic-mathematical modeling, as an efficient tool for supporting decisions, which ensures the selection of the most favorable supply options. This paper provides a dynamic model of optimized supply (at decentralized procurement of material and technical resources), which describes the possible options of arranging the logistics of organizational units of the armed forces. The criterion of global optimization is represented by a normalized performance indicator characterizing the level of provision of organizational units with material and technical resources. The proposed economic-mathematical model is an efficient tool for supporting decisions taken by logistics-management divisions of organizational units of armed forces - at multiple options of implementing the logistic processes and limited financial resources, which allows optimizing the level of provision of organizational units with required material and technical resources (for the entire planning period of supply, regarding change of needs, scope of funds allocated for logistics and logistic costs accompanying the supply process). (original abstract)